Innovative Natural Resource Management Technologies for Sustainable Agriculture - Sikka, A. K.; Prasad, Y. G.; Chaudhari, S. K. (Indian Farming, 2015)
The National Agricultural Innovation Project (NAIP) supported frontier research in consortium mode bringing together NRM and crop scientists to complete the innovation cycle. Basic and strategic research initiatives in the fields of nanotechnology, precision farming, GIS, DSS, climate change, soil, land quality management and water management resulted in the development of innovative technologies for conservation, efficient utilization, restoration of quality and resilience of natural resources to ensure an ecologically and environmentally sound agriculture. Postproject sustainability issues will be addressed by the NRM division of ICAR and innovations will be further nurtured for up-scaling so that benefits accrue to farming community in the country to ensure a better future for all.